Correlation Between Distance And Time of Travel and Utilization of Antenatal Care at Community Health Center, Gundih, Surabaya - Dewi Mardahlia (Health Notions, 2018)
The coverage of K4 pregnant women's visit in Surabaya for 2016 is 98.48%, the percentage is not far from the target SPM that has been set that is 100%. This study was conducted with the aim to know the relationship between the distance and travel time with the utilization of antenatal services in the working area Gundih public health center of Surabaya city. The research type is descriptive analytic with cross sectional approach. The research was conducted in Oktober-November 2017 in the working area of the gundih public health center in surabaya. The population in this research that all pregnant women in the working area of the public health center Gundih. Sampling is done by accidental sampling that is as many as 96 pregnant women who visited the public health center Gundih in the Surabaya city. Data collection was obtained through interviews with questionnaire guidance. The data analysis is univariate and bivariate. Results showed that of 96 pregnant women, the majority of the homes within close distance that is equal to 89 (92.2%) pregnant woman. While the travel time, the majority of pregnant woman choose fast as much as 87 (90.6%). Pregnant women who are in the public health center Gundih, the majority utilize antenatal care according to standar of pegnancy visit as much as 85 (88.5%). Based on the results of correlation between distance and time with the utilization of antenatal care, the value of p value is 0.006 and 0.031 (p≤0.05). This mean is that there is a significant correlation between distance and time with utilization of antenatal care in public health center Gundih in the Surabaya. The closer the distance between the house of pregnant women with health facilities then more. and more pregnant women who utilize antenatal care according to standard visits.Keywords: Distance, Travel time, Antenatal care